RoadKillJoy - Ng, Paul Xuan-En (Nanyang Technological University, 2024)
RoadKillJoy is a 2D animated comedy film about an armadillo and a hare trying to cross a road in the American Southwest desert, but the armadillo is so unlucky that he gets hit by traffic every time he tries. The project aims to create a funny and entertaining film with charming and dynamic animation, as well as tell a compelling story about overcoming problems despite your weaknesses. The film takes inspiration from classic American animation of the 1950s and 60s, adopting their animation techniques and ideologies while using modern digital technology.